1970
DOI: 10.1063/1.1658810
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Magnetic Order on Conduction Electrons and Phonons in Magnetic Semiconductors

Abstract: Magnetic correlations influence the energy of conduction electrons through the exchange coupling. A magnetization leads to a splitting of the band where, however, the states of the higher band are unstable against spin-flip with spin-wave production. The rather unknown ion-position dependence of the spin Hamiltonian couples the spins to the phonons. For weak spin-spin couplings an adiabatic principle is assumed. The effect of spin order on the phonon frequency, on the infrared and Raman spectra, and the isotop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…The spin-phonon coupling in magnetic semiconductors has been described by Baltensperger and Helman, 30 Baltensperger, 31 Brüesch and D'Ambrogio, 32 Lockwood and Cottam 33 and Wesselinowa and Apostolov. 34 These authors have shown that the frequency shift of a given phonon mode as function of temperature is determined by a spin-correlation function…”
Section: Spin-phonon Couplingmentioning
confidence: 99%
“…The spin-phonon coupling in magnetic semiconductors has been described by Baltensperger and Helman, 30 Baltensperger, 31 Brüesch and D'Ambrogio, 32 Lockwood and Cottam 33 and Wesselinowa and Apostolov. 34 These authors have shown that the frequency shift of a given phonon mode as function of temperature is determined by a spin-correlation function…”
Section: Spin-phonon Couplingmentioning
confidence: 99%
“…In magnetic materials, the frequency change of a phonon i with temperature can be written as [36][37][38][39][40] ( ) ( ) ( ) ( ) ( )…”
Section: Raman Phononsmentioning
confidence: 99%
“…Spin-phonon coupling has been described by many authors. [10][11][12][13] These authors have shown that the frequency shift of a given phonon mode is determined by spin-correlation function: ω = ω 0 + λ⟨S i • S j ⟩. Here, ω is the renormalized phonon frequency, ω 0 is eigenfrequency in the absence of spin-phonon coupling, λ is spin-phonon coupling constant.…”
mentioning
confidence: 99%